The Book of Daniel [videorecording (DVD)] - Henriksen, Lance, 1940-; Miano, Robert
In 605 B.C., Jerusalem was conquered by the Babylonians, and many of their best young men were taken into captivity, including Daniel. Daniel was taken to Babylon to serve its powerful King, Nebuchadnezzar. Daniel's example of boldness and faithfulness to God in the most difficult circumstances had eternal impact on the people and kings that he encountered. This Biblical epic tells the heroic and timeless stories of Daniel, as told in the Bible.